Communication technologies and their influence on language: the notion of convention revisited* - Žic Fuchs, Milena; Tuđman-Vuković, Nina; Broz, Vlatko (2013)
On the basis of a summation of topics that have emerged from research of text messaging in Croatian during the last ten years, other major questions and issues have also surfaced. In this paper we focus on the notion of convention, both from the linguistic as well as pragmatic point of view. Convention is viewed as a reflection of the complexity of language, seen not only as a cognitive phenomenon, or a cognitive ability, but also as being central to human interaction. Using text messaging as the basis for the research brought to light the importance of the technological medium, which plays a crucial role in the formation of convention. Due to the technological possibilities and limitations of the medium, new conventions appear in text messages, conventions that at the same time reflect linguistic, sociocultural and discourse/pragmatic factors. This implies that they are a reflection not only of linguistic convention, but also a reflection of the human social cognitive ability, essential in language use. On the basis of the examples analysed we also stress that the social cognitive ability is tailored to the medium of communication itself.
Projekt MZOS
ENG